Amazonía colombiana sujeto de derechos: análisis del fallo de la corte suprema de justicia sala de casación Civil stc 4360 de 2018 en el municipio de Cartagena del Chaira - Caquetá (2021)
In 2018 a group of 24 girls, boys and adolescents brought a tutelary action for protecting the “Supra-legal “rights, of having an environment, live and health, which me allegedly were violated by the Republic presidency, the ministries of environment and sustainable development and Agriculture and rural development, the special administrative unit of natural national parks of the governance of Amazonas, Caquetá, Guania, Guaviare, Putumayo and Vaupes, due to the increased deforestation in Colombian’s Amazon. The plaintiffs based their claim on the fact that the Colombian’s state signed the Paris’ agreement, whose objective was deal with the climate change and its negative effects, likewise with the Law 1753 of 2015, the government acquired national and international commitments of “reducing deforestation and emission of greenhouse gases in the context of climate change”, among which it is highlighted the duty of reducing “the net rate of deforestation to zero in Colombia’s Amazon for 2020” and that in accordance with the informs of early deforestation alerts -EDA, the deforestation in Colombia had an important increase in 2016 and 2017, which is alarming. The Superior Court of the Judicial District of Bogotá, upon analyzing the assumptions set forth by the plaintiffs of the action, indicated that the tutela was not the appropriate means to request the protection of the collective right to a healthy environment, since the legal system contemplates the popular action referred to in article 88 of the Political Constitution. Not satisfied with this, the judgment was challenged, the plaintiffs stated that the tutela action was a suitable means to request the protection and that it was also proven that in the specific case there was an irremediable damage. In the analysis of the challenge, the Supreme Court of Justice - Civil Cassation Chamber determined that the Colombian state has not efficiently faced the problem of deforestation in the Amazon and ordered the different administrative authorities, both national and territorial, to generate actions to mitigate deforestation in the region. Therefore, this paper will address in a broad manner the assumptions that are considered relevant and that motivated the ruling such as international instruments, domestic legislation and jurisprudence in light of the problem of deforestation in the Amazon, the philosophical concepts such as anthropocentrism, biocentrism and ecocentrism, biocentrism and ecocentrism in the socio-legal discussion on the environment and introduction legal subjectivity of the environment finally the analysis of the execution of the STC 4360 ruling of 2018 of the supreme court of justice civil cassation chamber facing the environmental situation in the municipality of Cartagena del Chairá- Caquetá, where the impact that the ruling has had when mitigating deforestation in the municipality will be verified.